Breeding Ewe Lambs: An Australasian Perspective - Paul R. Kenyon; Rene A. Corner-Thomas (Animals, 2022)
A number of potential advantages have been identified for breeding ewe lambs at 7 to 9 months of age, including increased lifetime productivity and profitability. However, breeding at this young age in extensive pastoral systems, such as in Australasia, can be associated with a number of disadvantages resulting in uptake of this management procedure being relatively low. This review highlights the known differences between ewe lamb and mature ewe reproductive performance, thus differing in their management. The review then summaries the scientific literature of factors that affect ewe lamb reproductive success, with a focus on recent studies conducted under extensive pasture-based conditions in Australasia. In particular, this review outlines the importance of ewe lamb live weight and body condition score on their productivity. The potential long-term consequences of breeding a ewe lamb at a young age in terms of her future success and that of her offspring to weaning are briefly outlined. In addition, the potential impacts of selecting progeny born to ewe lambs as future replacement ewes are discussed. Throughout this review, optimal management guidelines from prior to breeding the ewe lambs until rebreeding at 2 years of age are provided. Lastly, areas requiring future research are identified and discussed.